MoS2-MoO2 composite electrocatalysts by hot-injection method for hydrogen evolution reaction. (August 2017) - Wu, Chia-Ling; Huang, Po-Chia; Brahma, Sanjaya; Huang, Jow-Lay; Wang, Sheng-Chang
Abstract: Hydrogen has been considered as one of the most promising renewable energy for production and storage. Here, we report an efficient method to synthesize MoS2 -MoO2 composite by hot-injection method using MoO3 and S powder as precursors with oleic acid (OA) and oleylamine (OLA) as solvent, respectively. The X-ray diffraction shows the presence of the peaks from both MoS2 as well as MoO2 . With increasing reaction temperature and time, oleic acid reorganizes the octahedral units of MoO3 and gradually turn into low valence of Mo. After injecting S-precursor, OLA first reduces Mo-precursor to MoO2 as core, and then S atoms replace O atoms to form MoS2 as shell, eventually forming MoS2 -MoO2 core-shell structure. MoO2 with few-layer MoS2 can be observed by transmission electron microscope. A Tafel slope of 129 mV/dec is obtained for MoS2 -MoO2 composite, which is much better than MoS2 and MoO2 . The enhanced HER performance is attributed to the abundance active sites from MoS2 and the improved charge transfer direction by MoO2 .